Answer is:
He had a lovely finish.
_______________________________
Answer 1:
(x + 4)(x + 2)
Multiplying the binomials by distributing them,
we get;
= x² + 2x + 4x + 8
Adding up the like terms.
= x² + 6x + 8
The answer refers to the letter choice H.
_______________________________
Answer 2:
(x + 7)(x + 1)
Multiplying the binomials by distributing them,
we get;
= x² + 7x + 1x + 7
Adding up the like terms.
= x² + 8x + 7
The answer refers to the letter choice E.
_______________________________
Answer 3:
(x - 6)(x - 3)
Multiplying the binomials by distributing them,
we get;
= x² - 3x - 6x + 18
Adding up the like terms.
= x² - 9x + 18
The answer refers to the letter choice H.
_______________________________
Answer 4:
(x + 8)(x - 2)
Multiplying the binomials by distributing them,
we get;
= x² - 2x + 8x - 16
Adding up the like terms.
= x² + 6x - 16
The answer refers to the letter choice A.
_______________________________
Answer 5:
(x - 7)(x + 4)
Multiplying the binomials by distributing them,
we get;
= x² + 4x - 7x - 28
Adding up the like terms.
= x² - 3x - 28
The answer refers to the letter choice D.
_______________________________
Answer 6:
(x - 2)(x - 9)
Multiplying the binomials by distributing them,
we get;
= x² - 9x - 2x + 18
Adding up the like terms.
= x² - 11x + 18
The answer refers to the letter choice A.
_______________________________
Answer 7:
(2u + 4)(u + 1)
Multiplying the binomials by distributing them,
we get;
= 2u² + 2u + 4u + 4
Adding up the like terms.
= 2u² + 6u + 4
The answer refers to the letter choice L.
_______________________________
Answer 8:
(3u + 7)(u - 3)
Multiplying the binomials by distributing them,
we get;
= 3u² - 9u + 7u -21
Adding up the like terms.
= 3u² - 2u - 21
The answer refers to the letter choice O.
_______________________________
Answer 9:
(4u - 2)(5u - 1)
Multiplying the binomials by distributing them,
we get;
= 20u² - 4u - 10u + 2
Adding up the like terms.
= 20u² - 14u + 2
The answer refers to the letter choice V.
_______________________________
Answer 10:
(2u + 1)(9u - 5)
Multiplying the binomials by distributing them,
we get;
= 18u² - 10u + 9u - 5
Adding up the like terms.
= 18u² - u - 5
The answer refers to the letter choice E.
_______________________________
Answer 11:
(7u - 4)(3u + 6)
Multiplying the binomials by distributing them,
we get;
= 21u² + 42u - 12u - 24
Adding up the like terms.
= 21u² + 30u - 24
The answer refers to the letter choice L.
_______________________________
Answer 12:
(5u - 8)(4u - 4)
Multiplying the binomials by distributing them,
we get;
= 20u² - 20u - 32u + 32
Adding up the like terms.
= 20u² - 52u + 32
The answer refers to the letter choice Y.
_______________________________
Answer 13:
(2x + y)(x + 3y)
Multiplying the binomials by distributing them,
we get;
= 2x² + 6xy + 1xy + 3y²
Adding up the like terms.
= 2x² + 7xy + 3y²
The answer refers to the letter choice F.
_______________________________
Answer 14:
(3x - y)(8x - y)
Multiplying the binomials by distributing them,
we get;
= 24x² - 3xy - 8xy + y²
Adding up the like terms.
= 24x² - 11xy + y²
The answer refers to the letter choice I.
_______________________________
Answer 15:
(2x + y)(4x - 3y)
Multiplying the binomials by distributing them,
we get;
= 8x² - 6xy + 4xy - 3y²
Adding up the like terms.
= 8x² - 2xy - 3y²
The answer refers to the letter choice N.
_______________________________
Answer 16:
(5x - 2y)(3x + 4y)
Multiplying the binomials by distributing them,
we get;
= 15x² + 20xy - 6xy - 8y²
Adding up the like terms.
= 15x² + 14xy - 8y²
The answer refers to the letter choice I.
_______________________________
Answer 17:
(7x + 3y)(x + 2y)
Multiplying the binomials by distributing them,
we get;
= 7x² + 14xy + 3xy + 6y²
Adding up the like terms.
= 7x² + 17xy + 6y²
The answer refers to the letter choice S.
_______________________________
Answer 18:
(6x + 6y)(2x - 4y)
Multiplying the binomials by distributing them,
we get;
= 12x² - 24xy + 12xy - 24y²
Adding up the like terms.
= 12x² - 12xy - 24y²
The answer refers to the letter choice H.
_______________________________